THE INFLUENCE OF SHAPE FACTOR ON ROUGHNESS COEFFICIENT FOR OPTIMIZING CHANNEL PERFORMANCE IN IRRIGATION MODERNIZATION - Yustitianto Hernawan, Akbar
Indonesia has significant potential to become a leading agricultural nation; however, its productivity remains low. Over the past decade, agricultural productivity has decreased by 23.6%. Field investigations revealed that secondary and tertiary channels, designed based on hydraulic calculations, produce different outcomes from those observed in the field. Inaccurate channel design leads to channels being unable to convey the necessary water flow for crops. Enhancing the performance of irrigation channels is crucial for the modernization of irrigation in Indonesia, contributing to food self-sufficiency. This study aims to determine the influence of channel cross-sectional shapes on the Manning roughness coefficient. The research will be conducted through experimental methods using a physical model specifically designed for this study. The variables include channel roughness variations with wire diameters of 5mm, 2mm, and without wire, as well as trapezoidal channels with side slopes of 45?, 60?, 75?, and 90?. Flow rate measurements will be carried out using a Thomson weir or other appropriate measuring instruments based on the required capacity. The study results found that The greater the slope of the channel walls, the higher the roughness coefficient.